Minimum optimal trials and interval during measurement of maximal handgrip strength - Kim, Joon Yub; Kwon, Ki Bum; Song, Seong Hun; Kwon, Soon Sun; Kang, Byoung Youl; Kim, Dong Hee (Isokinetics and Exercise Science, 2018)
There are controversies regarding the optimal number of trials and intervals during required for testing of maximal handgrip strength. OBJECTIVES: To verify the minimum optimal number of trials (two versus three consecutive trials) and inter-effort interval (15, 30, 45 and 60-s) during the measurement of maximal handgrip strength. METHODS: One hundred healthy subjects, 51 males and 49 females, were enrolled. During the measurement of maximal handgrip strength, two consecutive trials were hypothesized to be the minimum necessary. We compared the maximal handgrip strengths between two and three consecutive trials at four different intervals (15, 30, 45, and 60-s). RESULTS: Irrespective of hand dominance, maximal handgrip strength was best measured with three consecutive trials rather than two at each interval (all p< 0.05 except 15-s intervals with the dominant hand). The values at 60-s interval (dominant hands: 40.6 kgf, non-dominant hands: 36.7 kgf) were significantly higher than at other intervals (all p< 0.05). CONCLUSIONS: Three consecutive trials with a 60-s interval might be the minimum needed for optimal measurement of maximal handgrip strength.
Keywords: grip strength test; Hand grip; interval; trial